Pembelajaran Sejarah pada Program Kejar Paket C - Windarsari, Ranulin; Sunardi, S.; Djono, D. (Universitas Muhammadiyah Surakarta, 2017)
This study is aimed to describe the implementation of learning history in kejar paket Cprograms. This study uses the descriptive qualitative method. Data were collected byinterviews, documentation, and observation. Data analysis technique use qualitativeanalysis inductive models with purposive sampling technique. The results of thisstudy are: first, planning learning history in kejar paket C program started fromin house training for educators in kejar paket C program which practiced in thepreparation of the learning device are appropriate to the curriculum; second, theimplementation of learning history in kejar paket C program involves three patternsof learning consisting of 20% face-to-face interaction, 30% tutorials, and 50%independent activity; third, constraints in the implementation of history learning inkejar paket C program is the readiness of learners in receiving learning materials,learning infrastructure, and the competence of educators in conveying the teachingof history; fourth, evaluation of learning history in kejar paket C program is equalto the formal school.